Muslims in Ireland : past and present - Scharbrodt, Oliver, 1976-; Sakaranaho, Tuula; Khan, Adil Hussain; Shanneik, Yafa; Ibrahim, Vivian (Edinburgh University Press, 2015)
Since 9/11, the interest in Muslims in Europe has increased significantly. There has been much public debate and academic research focused on Muslims living in larger Western European countries like Britain, France or Germany, but little is known of Muslims in Ireland. This book fills this gap, providing a complete study of this unexplored Muslim presence, from the arrival of the first Muslim resident in Cork, in the southwest of Ireland, in 1784 until mass immigration to the Republic of Ireland during the 'Celtic Tiger' period from the mid-1990s onwards. Muslim immigration and settlement in Ireland is very recent, and poses new challenges to a society that has perceived itself as religiously and culturally homogeneous. Ireland is also one of the least secular societies in Europe, providing a different context for Muslims seeking recognition by state and society. This book is essential for anyone who wants to understand the diversity of Muslim presences across Europe.